Curcumin alleviates experimental colitis in mice by suppressing necroptosis of intestinal epithelial cells - Zhong, Yuting; Tu, Ye; Ma, Qingshan; Chen, Linlin; Zhang, Wenzhao; Lu, Xin; Yang, Shuo; Wang, Zhibin; Zhang, Lichao (Frontiers in Pharmacology, 2023)
Curcumin, the primary bioactive substance in turmeric, exhibits potential therapeutic effects on ulcerative colitis. However, its mechanism for regulating necroptosis in colitis has not been fully elucidated. In this study, the effect of curcumin on experimental colitis-induced necroptosis of intestinal epithelial cells was investigated, and its molecular mechanism was further explored. We found that curcumin blocked necroptosis in a dose-dependent manner by inhibiting the phosphorylation of RIP3 and MLKL instead of RIP1 in HT-29 cells. Co-Immunoprecipitation assay showed that curcumin weakened the interaction between RIP1 and RIP3, possibly due to the direct binding of curcumin to RIP3 as suggested by drug affinity responsive target stability analysis. In a classical in vivo model of TNF-α and pan-caspase inhibitor-induced necroptosis in C57BL/6 mice, curcumin potently inhibited systemic inflammatory responses initiated by the necroptosis signaling pathway. Then, using a dextran sodium sulfate-induced colitis model in C57BL/6 mice, we found that curcumin inhibited the expression of p-RIP3 in the intestinal epithelium, reduced intestinal epithelial cells loss, improved the function of the intestinal tight junction barrier, and reduced local intestinal inflammation. Collectively, our findings suggest that curcumin is a potent targeted RIP3 inhibitor with anti-necroptotic and anti-inflammatory effects, maintains intestinal barrier function, and effectively alleviates colitis injury.